PENGEMBANGAN INSTRUMEN PEMBELAJARAN MENGGUNAKAN VIDEO HOLOGRAM 3D DALAM MASA HYBIRD - Arfa, Avini Nurazhimah; Julaeha, Siti; Awaludin, Aulia Ar Rakhman; Priambodo, Caka Gatot; Satria, Heri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study aims to develop learning instruments using 3D hologram videos in the Hybrid period. This research is research development (Research and Development). Research and development research methods are research methods used to produce a certain product, and test the effectiveness of certain products. Development research is a process or steps to develop a new product or improve existing products, which can be accounted for. To test the effectiveness of existing products so that they can function in the wider community, research is needed to test the effectiveness of these products. The product produced in this study is a learning media based on 3D hologram videos. This 3D hologram-based learning media research will be carried out at SMP Negeri 223 East Jakarta with the research subjects being Grade VIII students and the research object being 3D hologram video learning media in Mathematics. The results of the research are in the form of 3D hologram videos combined with inverted pyramids and smartphones as learning media using the Hannafin and Peck development model which consists of stages: needs assessment, design phase and development and implementation phase. phase). This media has gone through a validation process by media experts with assessment aspects in terms of appearance, language, and effectiveness and reliability.